Combination of GPS and RTS measurements for the monitoring of semi-static and dynamic motion of pedestrian bridge - Psimoulis, Panos; Peppa, Ioulia; Bonenberg, Lukasz; Ince, Sean; Meng, Xiaolin (2016)
GPS and accelerometers have been broadly used the last decade for the monitoring of flexible structures and bridges, while Robotic Total Station (RTS) has been successfully assessed for the monitoring of slow and dynamic motions. Further experimental studies have revealed specific drawbacks of the GPS (multipath, etc.) and RTS (clipping, etc.) monitoring techniques and how these can be surpassed by their combined use. In the current study, we assess the performance of the complementary use of GPS and RTS for the monitoring of the semi-static and dynamic displacement of a relatively rigid pedestrian bridge, with main modal frequency more than 1Hz. Two RTS and GPS receivers were synchronised monitoring the deflection of the two sides of the mid-span of the bridge, while pedestrians excited the bridge. Several excitations (walking, marching, jumping, etc.) were examined, causing semi-static and/or dynamic displacement of the bridge, and rotation of the deck, of different amplitude and frequencies. The analysis of the RTS and GPS time-series, which was based on spectral analysis and band-pass filtering of the time-series, resulted to low- and high-frequency component expressing the semi-static and dynamic displacement. Finally, the combination of the GPS and RTS time-series made possible the estimation of 1-4mm semi-static displacement, the 5-10mm dynamic displacement and the estimation of the main modal frequencies.